2011
DOI: 10.1371/journal.pone.0019622
|View full text |Cite
|
Sign up to set email alerts
|

α-Synuclein Expression Selectively Affects Tumorigenesis in Mice Modeling Parkinson's Disease

Abstract: Alpha Synuclein (α-Syn) is a protein implicated in mechanisms of neuronal degeneration in Parkinson's disease (PD). α-Syn is primarily a neuronal protein, however, its expression is found in various tumors including ovarian, colorectal and melanoma tumors. It has been hypothesized that neurodegeneration may share common mechanisms with oncogenesis. We tested whether α-Syn expression affects tumorigenesis of three types of tumors. Specifically, B16 melanoma, E0771 mammary gland adenocarcinoma and D122 Lewis lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 65 publications
1
25
0
Order By: Relevance
“…It has been reported that α-synuclein is expressed in melanoma (13) and that overexpressing it enhances the proliferation of B16 murine melanoma (14). However, scientific data regarding status and level of expression of the three major PD-related genes/proteins-α-synuclein/SNCA, LRRK2/PARK8, and parkin/PARK2-alongside one another in nevi and in early and advanced melanoma were not available.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that α-synuclein is expressed in melanoma (13) and that overexpressing it enhances the proliferation of B16 murine melanoma (14). However, scientific data regarding status and level of expression of the three major PD-related genes/proteins-α-synuclein/SNCA, LRRK2/PARK8, and parkin/PARK2-alongside one another in nevi and in early and advanced melanoma were not available.…”
Section: Resultsmentioning
confidence: 99%
“…Some of these genes have also been found to have a role in the development, progression and dissemination of melanoma or other malignant processes. For example, increased expression of NRCAM and STMN1, potentiates proliferation and migration of melanoma cells, while SNCA, a gene primarily expressed in the brain, but also in various tumors including ovarian, colorectal and melanoma, is involved in tumorigenesis (4548). …”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, PD patients have a higher risk of developing cancer [93], and in particular melanoma [94]. As a matter of fact, melanoma growth was increased in PD mice compared to wild-type mice [95,96]. Several hypotheses have been proposed to explain this finding.…”
Section: What Could Be the Relationship Between Glucosylceramide Gaumentioning
confidence: 99%